The Relevance of Recitals and Definitions in Preventing Ambiguity in International Contracts - Rangga Aditya Putra Jaya Wiratma; Wafda Vivid Izziyana (PT Justitia Legal Research, 2025)
International contracts are essential legal instruments in facilitating global business transactions, yet they often create interpretive ambiguities that may lead to costly disputes between parties from different jurisdictions. This study examines the relevance of Recitals and Definitions as contractual components designed to prevent ambiguity in international agreements. Using a normative-juridical methodology that incorporates literature review, comparative analysis, and case analysis of international arbitral decisions, the research investigates how these elements contribute to legal certainty and consistent interpretation. Recitals provide background, objectives, and the underlying intention of the contracting parties, serving as a crucial interpretative tool when disputes arise. Meanwhile, Definitions establish precise meanings of technical terms, thereby reducing multiple interpretations of contractual language. The findings reveal that both Recitals and Definitions significantly reinforce the principles of good faith, fair dealing, and pacta sunt servanda during contract implementation. Furthermore, despite interpretive differences between common law and civil law systems, their practical application remains highly relevant in drafting effective international contracts. Decisions from international arbitration bodies, such as the ICC and ICSID, demonstrate that Recitals and Definitions are frequently employed to determine the true intention of the parties in cases of interpretive conflict. Therefore, these components are not merely formal or supplementary content but foundational mechanisms for mitigating legal uncertainty and preventing disputes. The study recommends that legal practitioners improve the precision and consistency of contractual drafting, particularly in Recitals and Definitions, to enhance the enforceability and stability of international commercial relationships.